Exploring ayahuasca‐assisted therapy for addiction: A qualitative analysis of preliminary findings among an Indigenous community in Canada. (5th September 2019) - Argento, Elena; Capler, Rielle; Thomas, Gerald; Lucas, Philippe; Tupper, Kenneth W.
Abstract: Introduction and Aims: A previous observational study of ayahuasca‐assisted therapy demonstrated statistically significant reductions in self‐reported problematic cocaine use among members of an Indigenous community in Canada. This paper aims to qualitatively explore the impact of ayahuasca‐assisted therapy on addiction and other substance use‐related outcomes and elucidate the lived experiences of participants. Design and Methods: Qualitative interviews were conducted with 11 adult Indigenous participants of the ayahuasca‐assisted 'Working with Addiction and Stress' ceremonial retreats (June–September 2011). Semi‐structured interviews assessed experiences of participants following the retreats at 6‐month follow up. Thematic analysis of interview transcripts was conducted. Results: Narratives revealed that the retreats helped participants identify negative thought patterns and barriers related to their addiction in ways that differed from conventional therapies. All participants reported reductions in substance use and cravings; eight participants reported complete cessation of at least one substance at follow up. Increased connectedness with self, others and nature/spirit was described as a key element associated with reduced substance use and cravings. Discussion and Conclusions: This analysis expands upon prior quantitative results highlighting the therapeutic potential of ayahuasca‐assisted therapy and provides important contextual insights into why ayahuasca‐assisted therapy may have been beneficial for members of an Indigenous community seeking to address their problematic use of substances. Given limited efficacy of conventional treatments for resolving addiction issues, further research should investigate the role of ayahuasca and other psychedelic‐assisted therapies in enhancing connectedness and other key factors that may improve well‐being and reduce harmful substance use.